Readability Open-Ended Problems: Effects on the Learners’ Achievement Level of the Grade 7 Learners on Sets - Aimee Cadeliña Sumalpong; Douglas A Salazar; Jocelyn Amen Sumalpong (Universitas Sarjanawiyata Tamansiswa, 2026)
This study investigated readability-based open-ended problems’ effectiveness in improving Grade 7 learners’ Mathematics achievement level on Sets. Employing a quasi-experimental pretest-posttest nonequivalent groups design, two intact classes were compared: an experimental group (n=10) exposed to readability-based open-ended problems and a control group (n=10) using conventional word problems. The open-ended problems were contextually realistic, calibrated to Grade 7 via Flesch-Kincaid Readability Test, and allowed multiple correct answers to accommodate diverse abilities. Pretests, posttests, and interviews assessed performance and perceptions. Results revealed significant improvement in the experimental group, with most learners reaching proficient and advanced levels, whereas the control group had fewer advanced achievers. Nonparametric statistical tests confirmed significant differences favoring the experimental group. Qualitative findings indicated increased confidence and engagement, particularly among low-performing learners. The study concludes that integrating readability-based open-ended problems fosters enhanced understanding and problem-solving skills and recommends blending them with conventional problems for a fuller problem-solving repertoire.